Growth Volatility and Government Expenditure in Low and Middle Income Countries: A Dynamic Panel Analysis - Taner TURAN; Pelin VAROL IYIDOGAN (Transylvanian Review of Administrative Sciences, 2017)
We examine the relation between the governmentconsumption expenditure and outputgrowth volatility in 57 low and middle incomecountries by using both static and dynamic panelmethods. It seems that the results of thesemethods largely differ from each other. Contraryto some previous results reported in the literature,we present a strong evidence for a negativerelation between government expenditure andvolatility in low and middle income countries. Wealso conclude that the volatilities of governmentconsumption, trade openness and investmentare signifi cant in explaining the growth volatility.To have a more stable economy, policy makersin these countries should pay more attentionto some issues. In this context, we think thata change in the tax and expenditure system inorder to make automatic stabilizers work betterwould be helpful. Additionally, it is important tohave a sound fi scal and monetary position to effectivelycarry out countercyclical policies whenneeded. Moreover, adopting and implementingclear and fl exible rule-based economic policiesshould be considered. Finally, improving the institutionalstructure and policy making capacitymust be an ultimate aim to reduce the economicvolatility.